Capitalization of Productivity Growth in Urban Land Rent - John M. Hartwick (Queen's University, Department of Economics, 1993)
The first order effect of a productivity increment in the output sector of a monocentric city which increase wages in the city is exactly capitalized in the increment in land rent in the city. We observe this result in the "open city" model in which a worker's utility level in city i is determined outside of city i.
Keywords: 330